Missed opportunities for tuberculosis prevention among patients accessing a UK HIV service. (October 2018) - Rickman, Hannah M; Miller, Robert F; Morris-Jones, Stephen; Kellgren, Lusha; Edwards, Simon G; Grant, Alison D
United Kingdom guidelines recommend screening for and treatment of latent tuberculosis infection (LTBI) in HIV-positive patients at high risk of active tuberculosis (TB) disease, but implementation is suboptimal. We investigated potential missed opportunities to identify and treat LTBI among HIV-positive patients accessing a large HIV outpatient service in London. Case records of all adult patients attending our service for HIV care diagnosed with active TB between 2011 and 2015 were reviewed to determine whether they met criteria for LTBI screening and whether screening was undertaken. Twenty-five patients were treated for TB. Of 15 (60%) patients who started TB treatment ≥6 months after HIV diagnosis, 14 (93%) met UK guideline-recommended criteria for LTBI screening and treatment; only one (7%) had been screened for LTBI. Eight of these 15 (53%) patients had additional risk factors for TB which are not reflected in current UK guidelines. Of 15 patients treated for TB ≥6 months after diagnosis of HIV, 14 (93%) had not been screened for LTBI, suggesting missed opportunities for TB prevention. People living with HIV may benefit from a broader approach to LTBI screening which takes into account additional recognised TB risk factors and ongoing TB exposure.